2002
DOI: 10.1034/j.1399-0004.2002.610506.x
|View full text |Cite
|
Sign up to set email alerts
|

Deafness resulting from mutations in the GJB2 (connexin 26) gene in Brazilian patients

Abstract: Congenital deafness occurs in approximately 1 in 1000 live births. In developed countries about 60% of hearing loss is genetic. However, in Brazil most cases of hearing loss are due to environmental factors, such as congenital infections (mainly rubella), perinatal anoxia, kernicterus and meningitis. Recently, it has been demonstrated that the GJB2 gene is a major gene underlying congenital sensorial deafness. Mutations in this gene cause 10-20% of all genetic sensory hearing loss. One specific mutation, 35del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
(39 reference statements)
5
28
0
7
Order By: Relevance
“…In spite of the difference in sample selection criteria, the frequency of individuals presenting c.35delG mutation in the GJB2 gene (12.4%) in our study was similar to that found (13.9%) in the report of de Oliveira et al (2007). Our study agrees with these previous reports (de Oliveira, et al, 2007;Oliveira, et al, 2002;Piatto, et al, 2004), showing that the c.35delG mutation is the most frequent among causative mutations of hearing impairment in the Brazilian population. This is a common mutation causing HL in Caucasian populations, mainly from Mediterranean Europe and the United States, and seems to be rare in the Asian and African populations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In spite of the difference in sample selection criteria, the frequency of individuals presenting c.35delG mutation in the GJB2 gene (12.4%) in our study was similar to that found (13.9%) in the report of de Oliveira et al (2007). Our study agrees with these previous reports (de Oliveira, et al, 2007;Oliveira, et al, 2002;Piatto, et al, 2004), showing that the c.35delG mutation is the most frequent among causative mutations of hearing impairment in the Brazilian population. This is a common mutation causing HL in Caucasian populations, mainly from Mediterranean Europe and the United States, and seems to be rare in the Asian and African populations.…”
Section: Discussionsupporting
confidence: 81%
“…(de Oliveira, et al, 2007;Oliveira, et al, 2002;Piatto, et al, 2004). Our study comprises a sample that included sporadic and familial cases, and individuals presenting only with known deafness-related syndromes were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for cases of family hearing loss, among which the frequence of mutations in this gene was found to be of 50%, but also for sporadic cases, among which the frequence was a bit higher than 11% (approximately 1:9) (Oliveira et al, 2002). In Brazil, the prevalence of 0.97% of 35delG mutation carriers was found to be approximately 1:103 heterozigotes, in a survey carried out with 620 newborns in the region of Campinas-SP (Oliveira et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect the 35delG mutation we used the allele specific PCR method (AS-PCR), using primers and the aforementioned polymerase chain reaction -modification patented by CBMEG -UNICAMP. (Oliveira et al, 2002). This method easily differentiates the normal allele from the mutant and through two reactions it is possible to distinguish normal homozygotes, 35delG homozygote and heterozygote carriers of the 35delG mutation.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, performed in patients with hearing loss, mutations in the GJB2 gene were found in 33.5% of cases, and only the 35delG mutation was identified in 84.2% of mutant alleles 14 . The methodology used in the current study, AS-PCR and automated sequencing, was similar to the three above mentioned researches, but a variation was found in the frequency of the alleles with the 35delG mutation.…”
Section: Ic -Index Cases; Hl -Hearing Lossmentioning
confidence: 99%